Relación entre los préstamos y la morosidad de las entidades financieras de Loreto, periodo 2016 - 2020 - Gómez Bustamante, Lis Eliana (2022)
Loans and delinquencies are two variables to take into account for the health of the regional financial system, so their monitoring must be permanent. The objective of this research is to determine the relationship between loans and delinquency of financial entities in Loreto, in the period 2016 - 2020. Based on this purpose, the present study of Quantitative type, Correlational level and of Non-Experimental design. The investigation concludes that the loans granted by Loreto financial entities are not related to the level of delinquency shown in the period 2016 - 2020; endorsed by the results of the statistical test that shows that the Correlation Coefficient is r = - 0.251855532; very far from -1; likewise, the Determination Coefficient is R2 = 0.063431209; also, very far from 1; which shows that there is no association and determination between financial system loans and delinquency. On the other hand, Multiple Banking was the type of financial institution that granted the largest number of loans, maintaining an average balance of S / 1,525.60 million, equivalent to 66.26% of the total. The delinquency of financial entities in Loreto was 8.36% on average, exceeding the 5% considered normal by financial theory. The Agrobanco is the financial entity that reports the highest delinquency in the system, reaching 53.43% of the total, a very critical situation.